Identification and isolation of transcribed human X chromosome DNA sequences. - Kunkel, L M (1983)
A human X chromosome specific phage library has been used as a source of X-specific genomic DNA clones which hybridize with cellular RNA. Random cDNA clones were mapped for X chromosome sequence localization and 8 were identified as hybridizing to X chromosome Hind III fragments. All eight also hybridized with autosomal Hind III fragments. The X chromosome genomic sequences corresponding to two of these cDNA clones were isolated from a phage library constructed with the Hind III endonuclease digest products of X enriched DNA. One genomic DNA segment, localized to the short area of the X, shared sequence homology with at least one region of the human Y chromosome. The methodology developed represents a rapid means to obtain a specific genomic DNA clone from a single chromosome when multiple different genomic loci homologous to an expressed DNA sequence exist.